From margins to mainstream: HASA childhood neurodisability day 2025 spotlights inclusion and diversity - Zainudin, Muhamad Faizal; Md Yusof, Yusma Lyana (Faculty of Medicine, 2025)
Children with disabilities have long been marginalized, often overlooked and misunderstood. A study by UNICEF highlights persistent stigma, with some members of society believing these children should be hidden or may disrupt mainstream classrooms. This underscores the urgent need for greater awareness, advocacy, and cultural change.